Analisis Kadar Haemoglobin Dan Pola Nutrisi Terhadap Prestasi Belajar Mahasiswa Kebidanan - Esem, Odilia; Mindarsih, Theresia (Universitas Prima Indonesia, 2024)
Learning achievement is an important indicator in the world of education, which is usually measured through test scores, cumulative achievement index (GPA), and other parameters that reflect students' academic abilities. Various factors can influence learning achievement, such as anemia and nutritional patterns. This study aims to determine the relationship between hemoglobin levels and nutritional patterns and learning achievement. This research uses a descriptive correlational research type with a cross sectional research design with a population of 249 people and a sample of 124 people. The sampling technique used was Proportional Simple Random Sampling, using univariate and bivariate analysis tests. The independent variables are hemoglobin levels and nutritional patterns and the dependent variable is the student achievement index using the Chi Square Test. The results of the analysis using spearmanrank obtained a p value of 0.000. Because the p value of 0.000 is less than 0.05 (p<0.05), this means that statistically there is a relationship between hemoglobin levels and learning achievement. The results of the analysis using spearmanrank obtained a p value of 0.046. Because the p value of 0.046 is smaller than 0.05 (p<0.05), this means that statistically there is a relationship between nutritional patterns and hemoglobin levels. Educational institutions should provide a routine health examination program that includes measurement of hemoglobin levels. This is important to detect cases of anemia early and carry out the necessary interventions before the condition affects student academic performance.